2020
DOI: 10.37380/jisib.v10i3.640
|View full text |Cite
|
Sign up to set email alerts
|

Financial intelligence: Financial statement fraud in Indonesia

Abstract: Indonesia is currently in an honesty crisis, especially in financial governance, bothin government and private institutions. Our study uses the concept of financial intelligence toidentify and collect information related to financial affairs in an organization. We use theopinions of 76 auditors regarding various fraudulent attempts, both with fraudulent financialstatements and other corrupt practices in organizations in Indonesia. Our important finding isthat small companies are more likely to commit fraud due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Nonetheless, both of these aspects are crucial; while the accuracy of the financial report is critical (Chen et al, 2011), responsible corporate governance enhances vigilance and prevents fraud (Thejls Ziegler, 2022). The recent financial mishaps and the questionable financial statements have compelled the business community to adhere to financial and accounting standards, making forensic accounting the only viable alternative for rebuilding investors' confidence (Ikbal et al, 2020). This reinforces our conclusion that forensic accounting is essential to strengthening the credibility of financial reporting, with the promotion of responsible corporate governance being the most significant aspect of forensic accounting.…”
Section: Perceived Benefits Of Forensic Accountingsupporting
confidence: 75%
“…Nonetheless, both of these aspects are crucial; while the accuracy of the financial report is critical (Chen et al, 2011), responsible corporate governance enhances vigilance and prevents fraud (Thejls Ziegler, 2022). The recent financial mishaps and the questionable financial statements have compelled the business community to adhere to financial and accounting standards, making forensic accounting the only viable alternative for rebuilding investors' confidence (Ikbal et al, 2020). This reinforces our conclusion that forensic accounting is essential to strengthening the credibility of financial reporting, with the promotion of responsible corporate governance being the most significant aspect of forensic accounting.…”
Section: Perceived Benefits Of Forensic Accountingsupporting
confidence: 75%
“…Business areas in which CT was researched at the business function level include accounting, marketing, human resources and business opportunity identification. Scholars showed that the application of CT in accounting allows for the appropriate construction of accounting systems, which increases profits thanks to appropriate information (Ikbal, Paminto, Darma, Ulfah, & Ilmi, 2020). Others revealed that the application of CT skills to marketing – especially advertising and promotion – increase their effectiveness by enabling businesses to reach intended target groups more efficiently (Kraus, Harms, & Fink, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The samples used in this instrument test are customers at PT. ASABRI (Persero) a total of 30 respondents (Ikbal et al, 2020).…”
Section: Validity Test Resultsmentioning
confidence: 99%